Bibliometric Analysis of Higher-Order Thinking Skills Based on Google Scholar, Crossref, and Scopus - Deda, Yohanis Ndapa (Jurnal VARIDIKA, 2023)
Higher-order thinking (HOT) skills are needed to analyze, evaluate, and solve problems. HOTS is an essential ability that students must have as a provision for the future and the 21st Century. However, no bibliometric research has linked Crossref, Scopus, and Google Scholar (GS) preferences on Harzing's Publish or Perish (PoP) software. This research aims to identify search preferences in PoP software version 8.9.4554.8721. The sample critical phrases entered in the preference menu are Higher-order thinking skills (HOTs) with a time range from 2018 to 2023. The library study research method used is bibliometric analysis. Metadata in the form of RIS/Refmanager files obtained from PoP is used to visualize data through VosViewer software. CSV data is used to identify top authors and top sources based on each preference. The phrases or keywords used were "HOTs," Mathematics" in GS, Crossref, and Scopus preferences. The results show four clusters of HOTS: ability, student, effect, and category. The top authors cited in Scopus are Hadi et al., Hobri et al. in GS, and Ichsan et al. in Crossref. HOTS needs to be researched more from various perspectives and methods. We recommend that future HOTS research be linked to real life to bridge the quite abstract concept of HOTS.